Emerging Word Games to Improve Young Learners' Vocabulary Skills in Ambonese Islamic School - Rohib Adrianto Sangia (Universitas Pendidikan Mandalika, 2022)
This study aims to determine the implementation of word games and their impact on student learning outcomes in learning new vocabulary in grade VII Mts Hasyim Asyari Ambon academic year 2020/2021. This research was conducted in three cycles. Using word games as a methodology in teaching English vocabulary starts with the preliminary activities of the teacher opening the class, preparing word game activities, and conveying the objectives of the material. Then in the core activity, the teacher applies the word games. The teacher gives instructions about the rules and activities of word games. In the closing activity, the teacher asks students to express their difficulties and problems when doing word games. The subsequent finding is that student learning outcomes increase each cycle, wherein only five students, or 20%, have completed the pre-cycle using conventional methods. During the first cycle, learning was carried out using word game methodologies. The number of students who achieved completeness threshold rose to 16 people or 64%. In the last cycle, all students can complete the post-test with the same methodology. It shows that using the word games methodology to deliver vocabulary learning materials has significantly improved student learning outcomes.